Jonah 2: a death liturgy for the doomed prophet - Kozlova, Ekaterina E. (The journal of Hebrew scriptures, 2020)
The use of fauna- and flora-based symbolism in ancient lament literature is a well-attested phenomenon. This article focuses on this symbolism in Jonah 2, exploring nature’s ritual agency in preparing Jonah for his entombment in the heart of the sea. In conclusion, the article considers how Jonah 2 can serve as an interpretive lens for Jonah 3 and 4, particularly their views on death and life.